ASPEK HUKUM LINGKUNGAN HIDUP DALAM UPAYA MENCEGAH TERJADINYA KERUSAKAN DAN PENCEMARAN LINGKUNGAN HIDUP DI INDONESIA - Arifin Ma'ruf (Wacana Hukum, 2018)
In Article 33 paragraph (3) of the 1945 Constitution which states that: 'earth and water and natural resources contained therein is controlled by the State and used for the greatest prosperity of the people ". The provision is further stipulated in Law No. 23 of 2009 on the Protection and Environmental Management, in the provisions of Article 57 paragraph (1) regulates the procedure for the maintenance of the environment, namely: "Maintenance of the environment is done through the efforts of: a. conservation of natural resources; b. reserves of natural resources; and / or c. conservation atmosphere. "But in fact the implementation of the article can not be implemented to the fullest. The use of earth and water and natural resources for the prosperity of the people in Indonesia has not run well, this is caused by the rampant environmental pollution rife Indonesia, water pollution, air pollution and soil contamination. Pollution and destruction of the environment is one of the serious threat to the conservation of the environment in Indonesia. Disturbed environmental balance needs to be restored function as the giver of life and welfare benefits society by improving environmental protection, community development and optimization of environmental law enforcement, it aims to maintain the existence of nature and aimed at solving environmental problems in Indonesia, especially the caused by human activity. in this case could penegakanya through civil, administrative or criminal law, so that it can cope with and take action against perpetrators of pollution, and the destruction of the environment and create a good environment, healthy, beautiful and comfortable for all people.